2019
DOI: 10.1016/j.rbo.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Concordância intra e interobservador com relação ao sistema de classificação de Walch para artrose da articulação do ombro

Abstract: Objective  To evaluate the inter- and intraobserver agreement regarding the Walch classification system for shoulder arthritis. Methods  Computed tomography scans of the shoulder joint of adult patients were selected between 2012 and 2016, and they were classified by physicians with different levels of expertise in orthopedics. The images were examined at three different times, and the analyses were evaluated by the Fleiss Kappa index to verify the intra- and interobserver agreement. Results  The Kappa index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…However, since the modified Walch classification was published, several authors have reported lower kappa scores for both interobserver and intraobserver reliabilities than Bercik et al, suggesting that the reliability may not be as high as initially predicted. 29,30…”
Section: The Modified Walch Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the modified Walch classification was published, several authors have reported lower kappa scores for both interobserver and intraobserver reliabilities than Bercik et al, suggesting that the reliability may not be as high as initially predicted. 29,30…”
Section: The Modified Walch Classificationmentioning
confidence: 99%
“…Although some evidence supports moderate reliability of the modified Walch classification, 33 there remains evidence indicating poor reproducibility using this classification. 29,30 Low reproducibility implies imperfect understanding of pathology that may influence treatment plans and interpretations of clinical outcomes. 9 Thus, we predict that the classification of glenohumeral osteoarthritis will transition toward simple numerical values that describe the precise amount and direction of subluxation, amount of glenoid erosion, and degrees of inclination.…”
Section: What the Future Holdsmentioning
confidence: 99%